2002
DOI: 10.1021/bp010126f
|View full text |Cite
|
Sign up to set email alerts
|

Solubility and Diffusion of Nitrogen in Maltodextrin/Protein Tablets

Abstract: The gas transport properties of compacted tablets consisting of an amorphous mixture of maltodextrin and sodium caseinate were studied by dissolving nitrogen gas in the tablets and then determining the gas release over time as a function of temperature and water activity. Gas was dissolved in the tablet matrix by heating the tablets under pressure, generally to temperatures above the glass transition temperature of the matrix, holding them at these conditions for a specified time and then rapidly cooling them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…The non-ergodic character of the glassy state in addition impacts the solubility of small molecules in glasses, as different realizations of the glassy state (i.e. glassy matrices with different thermal histories) may have different effective gas solubilities [94]. In addition, the small molecules themselves may act as plasticizer (or, under specific conditions, as antiplasticizer), and impact the phase behavior of the matrix [95,96].…”
Section: Molecular Interactions Water Vapor Sorption and Transport Pmentioning
confidence: 99%
“…The non-ergodic character of the glassy state in addition impacts the solubility of small molecules in glasses, as different realizations of the glassy state (i.e. glassy matrices with different thermal histories) may have different effective gas solubilities [94]. In addition, the small molecules themselves may act as plasticizer (or, under specific conditions, as antiplasticizer), and impact the phase behavior of the matrix [95,96].…”
Section: Molecular Interactions Water Vapor Sorption and Transport Pmentioning
confidence: 99%
“…2 On this basis, Santos et al (2014a) investigated the T g of Lactobacillus delbrueckii subsp. Considering that T g are also indicative of molecular mobility of small molecules within the sample (i.e., water, gases, and small organic molecules) (Schoonman et al, 2002), NIR is likewise a useful tool to determine T − T g (Santos et al, 2014c). They reported that the first overtone of the stretching OH 2.…”
Section: Use Of Prebiotics As Protectants Of Startersmentioning
confidence: 99%
“…These data demonstrate that DLPC degradation rate in the different sugar formulations does not correlate with state (glass or rubber) of the sugar amorphous matrix. Considering that the diffusion of lipids would likely be affected by the physical state of the matrix, this result suggests that the translational mobility of the lipid molecules was not dictating the rate of degradation, but it does not rule out a role for small molecules (e.g., O 2 ) that are able to diffuse through the amorphous matrix, 42,51,52 and are less affected by the physical state of the matrix.…”
Section: Effect Of the Lyoprotectant (Trehalose Sucrose Or Sorbitol)mentioning
confidence: 93%